High‐resolution MRI and diffusion‐weighted imaging of the human habenula at 7 tesla. Issue 4 (20th November 2013) - Strotmann, Barbara; Heidemann, Robin M.; Anwander, Alfred; Weiss, Marcel; Trampel, Robert; Villringer, Arno; Turner, Robert
Abstract : Purpose: To investigate the feasibility of discriminating the habenula in human brain using high‐resolution structural MRI and diffusion‐weighted imaging at 7 Tesla (T). Materials and Methods: MRI experiments included a MP2RAGE and GRE sequence to acquire quantitative parameter maps of T1, T2*, and a calculated proton density map and the combined approach of zoomed and parallel imaging (ZOOPPA) to obtain dw images. Probabilistic tractography algorithms were used to identify multiple fiber orientations in submillimetre voxels, and constrained spherical deconvolution to resolve orientations in regions where fibers cross. Results: Maps of T1, T2*, and proton density showed high contrast of the human habenula. The lateral habenula and its commissure can be distinguished from medial habenula and adjacent tissue. DWI data with 0.7 mm isotropic resolution revealed that fiber populations differ in medial and lateral habenula and two major fiber bundles that connect habenular nuclei with forebrain structures and brainstem. Conclusion: High resolution 7T MR imaging of the human habenula provides sufficient signal‐to‐noise and contrast to enable identification of the lateral and medial nuclei. In vivo high resolution DWI at 7T is able to distinguish between lateral and medial habenula, and to detect major fiber tracts that connect the habenula with other brain areas.J. Magn. Reson. Imaging 2014;39:1018–1026. ©2013 Wiley Periodicals, Inc .